2021
DOI: 10.3390/ma14061336
|View full text |Cite
|
Sign up to set email alerts
|

On the Microstructural, Mechanical and Tribological Properties of Mo-Se-C Coatings and Their Potential for Friction Reduction against Rubber

Abstract: Friction and wear contribute to high energetic losses that reduce the efficiency of mechanical systems. However, carbon alloyed transition metal dichalcogenide (TMD-C) coatings possess low friction coefficients in diverse environments and can self-adapt to various sliding conditions. Hence, in this investigation, a semi-industrial magnetron sputtering device, operated in direct current mode (DC), is utilized to deposit several molybdenum-selenium-carbon (Mo-Se-C) coatings with a carbon content up to 60 atomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…By contrast, the decrease in friction for the MoSeC films was evident at the HL regime between 2.3% and 5.2%. According to previous studies, these properties of the TMD coatings were found only in the case of the MoSeC films due to their better tribological properties [30]. Most likely, during the mixed lubrication regime, the sliding speed was not yet high enough for the film to have hydrodynamic effects with lower friction.…”
Section: Tribology Testingmentioning
confidence: 92%
“…By contrast, the decrease in friction for the MoSeC films was evident at the HL regime between 2.3% and 5.2%. According to previous studies, these properties of the TMD coatings were found only in the case of the MoSeC films due to their better tribological properties [30]. Most likely, during the mixed lubrication regime, the sliding speed was not yet high enough for the film to have hydrodynamic effects with lower friction.…”
Section: Tribology Testingmentioning
confidence: 92%
“…The silanization reaction index is an important indicator of silica silane modification. The larger the silanization reaction index, the higher the degree of silanization reaction and the better the overall performance of the rubber compound [27][28][29][30][31][32][33][34][35].…”
Section: Testing Methodsmentioning
confidence: 99%
“…According to the proportion of the silanization reaction, the high-temperature ethanol–water mixed vapor was sprayed onto the metal surface. The mixing conditions of the mixer were qualitatively simulated [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Mechanistic Studymentioning
confidence: 99%